2017
DOI: 10.1016/j.solmat.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Titanium diboride ceramics for solar thermal absorbers

Abstract: Titanium diboride (TiB2) is a low-density refractory material belonging to the family of ultra-high temperature ceramics (UHTCs). This paper reports on the production and microstructural and optical characterization of nearly fully dense TiB2, with particular interest to its potential utilization as novel thermal solar absorber. Monolithic bulk samples are produced starting from elemental reactants by a two-step method consisting of the Self-propagating High-temperature Synthesis (SHS) followed by the Spark Pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 63 publications
(115 reference statements)
0
28
0
Order By: Relevance
“…However, SiC is not spectrally selective as it has a high spectral emittance [8,9]. Transition metal carbides, nitrides and borides of column IV have been subject of many investigations due to their inherent spectral selectivity [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Among these materials, titanium carbide could be a good candidate because it is spectrally selective and it has good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, SiC is not spectrally selective as it has a high spectral emittance [8,9]. Transition metal carbides, nitrides and borides of column IV have been subject of many investigations due to their inherent spectral selectivity [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Among these materials, titanium carbide could be a good candidate because it is spectrally selective and it has good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The base properties outlined in this and previous studies [13,14,16,17,28] can be the starting point for future development of ground-breaking materials with specific properties tunable according to the needs imposed by the application.…”
Section: Advantages In the Use Of Uhtc As Solar Absorbersmentioning
confidence: 90%
“…The increasing interest in these materials is due to their unique combination of properties, including the highest melting points of any group of materials, >3000°C, elevate strength at extreme temperature, like 600-800 MPa at 1500-2100°C [11], high thermal conductivity, 80-110 W/mK up to 2000°C [12] and chemical stability. Recently, it has been found that most of these compounds also have the characteristic of being intrinsic solar selective materials [13][14][15][16][17][18][19], but the understanding of the optical properties of these materials is still very scanty, especially at high temperature. UHTCs have thus the potential to be suited for application in high temperature solar receivers, once their basic properties have been properly investigated and correlated to the bulk and surface characteristics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations